Effects of ruminally protected choline and dietary fat on performance of finishing heifers - Bindel, D.J.; Wessels, R.H.; Loest, C.A.; Drouillard, James S.; Titgemeyer, Evan C. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
A 120-day finishing study utilizing 318 heifers (753 lb initial body weight) examined the effects of ruminally protected choline in diets with no tallow or 2 or 4% of supplemental tallow. Heifers were fed a finishing diet based on a mix of steam-flaked and dry- rolled corn; encapsulated choline (20, 40, or 60 g/head/day, supplying 5, 10 or 15 g choline/head/day) was top-dressed to the diet or not added. Dry matter intake decreased linearly with inclusion of fat (P<.05) but was not affected significantly by addition of choline. Daily gains also decreased linearly (P<.05) with fat addition. Choline supplementation increased gain (linear, P<.1; qua dratic, P<.05), with the greatest increase occurring for the first 20 g increment encapsulated choline/day. Likewise, feed efficiency improved (P<.1) with supplemental choline. Again, the greatest response occurred for the first 20 g/day. Kidney, pelvic, and heart fat and yield grade both increased linearly (P<.1) with fat supplementation. The percentage of carcasses grading USDA Choice decreased (linear, P<.05; quadratic, P<.1) when choline was added at 60 g/day. Hot carcass weight, marbling, dressing percent, and 12th rib fat thickness were not affected significantly by either fat or choline. Ruminally protected choline can improve average daily gain and feed efficiency of finishing cattle.
Keywords: Beef; Choline; Fat; Finishing; Heifers; Performance; Carcass